2021
DOI: 10.24843/eja.2021.v31.i05.p01
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility dan Free Cash Flow pada Tax Avoidance

Abstract: Tax avoidance is the taxpayers effort to reduce tax payments to the government made by taxpayers, especially companies because they do not violate regulations regarding taxation. This study aims to examine the effect of corporate social responsibility and free cash flow on tax avoidance which is proxied by using the cash effective tax rate (CETR). This research was conducted at manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2019 period. The sample used was 68 companies with a total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
1
1
0
1
Order By: Relevance
“…The results of this study are in contrast to Dakhli (2022)shows CSR has a positive and significant effect on tax avoidance. The results of this study are in line with Dewi & Putri (2021) show that CSR has no effect on tax avoidance. The CSR expense report does not fully describe the condition of the company so that it cannot be used as a guarantee for the company to carry out tax avoidance.…”
Section: H 3 : Csr Has An Effect On Tax Avoidancesupporting
confidence: 89%
See 1 more Smart Citation
“…The results of this study are in contrast to Dakhli (2022)shows CSR has a positive and significant effect on tax avoidance. The results of this study are in line with Dewi & Putri (2021) show that CSR has no effect on tax avoidance. The CSR expense report does not fully describe the condition of the company so that it cannot be used as a guarantee for the company to carry out tax avoidance.…”
Section: H 3 : Csr Has An Effect On Tax Avoidancesupporting
confidence: 89%
“…The high cost of corporate CSR, makes companies do tax avoidance. Dewi & Putri (2021)state that CSR has no effect on tax avoidance. CSR costs reported by the company do not fully describe the condition of the company so that it cannot be used as a guarantee for the company to avoid taxes.…”
Section: Institutional Ownershipmentioning
confidence: 95%
“…Oktamawati (2017) concluded that executive character is positively associated with tax avoidance. It differs from Dewi & Sari (2015), who found that executive character is negatively associated with tax avoidance. At the same time, Kartana & Wulandari (2018) and Tandean & Winnie (2016) concluded that executive character is not associated with tax avoidance.…”
Section: Introductionmentioning
confidence: 64%
“…Teori keagenan atau agency theory mengkaji desain kontrak antara principal dan agen untuk mendorong agen rasional bertindak atas nama principal ketika kepentingan agen akan berlawanan dengan kepentingan principal (Scott & O'Brien, 2019). Dewi & Putri (2021) menyatakan hubungan antara principal dan agen dapat menyebabkan ketidakseimbangan informasi antara principal dan agen (informasi asimetris) karena agen memiliki lebih banyak informasi atau pengetahuan mengenai perusahaan daripada principal.…”
Section: Landasan Teori Agency Theoryunclassified